Factores motivacionales en la comprensión de textos en inglés en estudiantes de cuarto grado de secundaria en instituciones educativas públicas del distrito de Punchana 2021 - Ipanama Mendoza, Heidy Milagros (2024)
The objective of the present study was to explain the influence of motivational factors in fourth year students’ English reading comprehension at public schools of Punchana district 2021. The research type was explanatory with field study, contemporary transectional, and multivariate designs. The study population consisted of 643 students and a stratified sample with a proportional allocation of 241. Results show that the mean score in motivational factors was 48.30 on a scale transformed to 100. In reading comprehension, the mean score was 10.36 out of 20. That is, they are in starter level of achievement. Likewise, in its dimensions: Getting information (12.75, in process), inferencing and interpreting (9.16, starter) and evaluation of text format, content and context (7.99, starter). In conclusion, Spearman Rho test results show that there is no correlation between motivational factors and English reading comprehension as the correlation is negative and p-value = .885 > α = 0.05. Therefore, there was no need to carry out any regression analysis.